Asam Laurat Minyak Maggot (Hermetia illucens L.) Sebagai Bahan Dasar Kosmetik - Chardia Nectarina Amandava Nugrahati; Rudy Agung Nugroho (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2025)
The development of sustainable and environmentally friendly cosmetic ingredients continues to be developed. One of the important ingredients in cosmetics is Lauric acid.  Lauric acid with high content can be obtained from the black soldier fly (Hermetia illucens L.) larva oil or BSFL oil.  The aim of the study was to reveal the potential of lauric acid from BSFL oil as an important ingredient in cosmetics. From previous research, it was stated that BSFL oil contains about 17-22% lauric acid even higher depends on their substrate to growth. The relatively high content of lauric acid in the BSFL oil, provides better advantages, lower toxicity and environmentally friendly as antibacteria, antifungal, and a biosurfactant compared to surfactants from petroleum. The use of BSFL oil as a sustainable source of lauric acid is attractive, because these insects can grow in various organic waste substrates, so the production process is more cost-effective and environmentally friendly. In addition, lauric acid as a biosurfactant exhibits properties of surface and interfacial activity, emulsification, wetting, and foaming, which are critical for the performance of various cosmetic products. In addition, lauric acid biosurfactants have been shown to have good antibacterial and antioxidant properties.